A Rule-based System for Programming Self-Organized Sensor and Actor Networks - Dressler, Falko; Dietrich, Isabel; German, Reinhard; Krueger, Bettina (Elsevier Computer Networks)
We describe a programming scheme for massively distributed systems that are assumed to self-organize according to a given set of simple rules. The focus of this investigation is operation and control in Sensor and Actor Networks (SANETs). The main issues addressed by self-organization techniques are scalability, network lifetime, and real-time support. In the literature, biological principles are often cited as inspirations for technical solutions, especially in the domain of self-organization. We developed a system named Rule-based Sensor Network (RSN) according to the observed communication and control behavior in cellular communication. Cellular signaling cascades allow the event-specific reaction initiated by individual cells in collaboration with their direct neighbors. Information between cells are transmitted via proteins and result in the cascade of protein-protein or protein-DNA interactions to produce a specific cellular answer, e.g. the activation of cells or the transmission of mediators. These processes are programmed in every individual cell and lead to a coordinated reaction on a higher organization platform. We transferred these mechanisms to operation and control in SANETs. In particular, a rule-based processing scheme relying on the main concepts of cellular signaling cascades has been developed. It relies on simple local rules and provides problem specific reaction such as local actuation control and data manipulation. We describe this RSN technology and demonstrate comparative simulation results that show the feasibility of our approach.

Materielle Ressourcen – oder: Warum, wozu und wie haben und nutzen wir Güter? - Schlegel-Matthies, Kirsten; Methfessel, Barbara; Bigga, Regine (Haushalt & Bildung)

Frühe Hilfen rechnen sich - Wagenknecht, Inga; Meier-Gräwe, Uta; Fegert, Jörg M. (Frühförderung interdisziplinär)

How pre- and postnatal risk factors modify the effect of rapid weight gain in infancy and early childhood on subsequent fat mass development: results from the Multicenter Allergy Study 90. - Karaolis-Danckert, N; Buyken, Anette; Kulig, M; Kroke, A; Forster, J; Kamin, W; Schuster, A; Hornberg, C; Keil, T; Bergmann, RL; Wahn, U; Lau, S (Am J Clin Nutr)

Association of prepubertal body composition in healthy girls and boys with the timing of early and late pubertal markers - Buyken, Anette; Karaolis-Danckert, Nadina; Remer, Thomas (The American Journal of Clinical Nutrition)

Consumption of sugar-sweetened beverages and its association with nutrient intakes and diet quality in German children and adolescents - Libuda, Lars; Alexy, Ute; Buyken, Anette; Sichert-Hellert, Wolfgang; Stehle, Peter; Kersting, Mathilde (British Journal of Nutrition)

Association between long-term consumption of soft drinks and variables of bone modeling and remodeling in a sample of healthy German children and adolescents - Libuda, Lars; Alexy, Ute; Remer, Thomas; Stehle, Peter; Schoenau, Eckhard; Kersting, Mathilde (The American Journal of Clinical Nutrition)

Konsum von Erfrischungsgetränken und Entwicklung des Körpergewichts im Kindes- und Jugendalter – Gibt es eine Verbindung? - Libuda, Lars; Alexey, U.; Stehle, P.; Kersting, M. (Aktuelle Ernährungsmedizin)

DONALD News: Erfrischungsgetränke und Ernährungsqualität. - Libuda, Lars; Kersting, M. (Ernährungsumschau)

Effects of Breastfeeding on Trajectories of Body Fat and BMI throughout Childhood - Buyken, Anette; Karaolis-Danckert, Nadina; Remer, Thomas; Bolzenius, Katja; Landsberg, Beate; Kroke, Anja (Obesity)

Prevalence of Chronic Complications, Metabolic Control and Nutritional Intake in Type 1 Diabetes: Comparison Between Different European Regions - Toeller, M.; Buyken, Anette; Heitkamp, G.; Berg, G.; Scherbaum, W. (Hormone and Metabolic Research)

Ernährungsbildung in Unterricht und Schulprofil. Essen und Trinken in der Schule – Bildungschance und Beitrag zu sozialer Gerechtigkeit - Schlegel-Matthies, Kirsten (Ernährung, Kultur, Lebensqualität. Wege regionaler Nachhaltigkeit)

Private Lebensführung als Umgang mit Komplexität - ein schwer operationalisierbares Bildungsziel - Methfessel, B.; Ritterbach, U.; Schlegel-Matthies, Kirsten (.): Schwer messbare Kompetenzen. Herausforderungen für die empirische Fachdidaktik)

Konsumentinnen und Konsumenten - politisch denkende und moralisch handelnde Akteure - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Cleavage in the γ-subunit of the epithelial sodium channel (ENaC) plays an important role in the proteolytic activation of near-silent channels - Diakov, Alexei; Bera, Katarzyna; Mokrushina, Marianna; Krueger, Bettina; Korbmacher, Christoph (The Journal of Physiology)
The mechanisms by which proteases activate the epithelial sodium channel (ENaC) are not yet fully understood. We investigated the effect of extracellular proteases on rat ENaC heterologously expressed in Xenopus laevis oocytes. Application of trypsin increased ENaC whole-oocyte currents by about 8-fold without a concomitant increase in channel surface expression. The stimulatory effect of trypsin was preserved in oocytes expressing alphagamma-ENaC, but was abolished in oocytes expressing alphabeta-ENaC. Thus, the gamma-subunit appears to be essential for channel activation by extracellular proteases. Site-directed mutagenesis of a putative prostasin cleavage site in the extracellular loop of the gamma-subunit revealed that mutating the 181Lys residue to alanine (gammaK181A) increases ENaC baseline whole-oocyte currents, decreases channel surface expression, and largely reduces the stimulatory effect of extracellular proteases (trypsin, chymotrypsin and human neutrophil elastase). In single-channel recordings from outside-out patches we demonstrated that the gammaK181A mutation essentially abolishes the activation of near-silent channels by trypsin, while a stimulatory effect of trypsin on channel gating is preserved. This apparent dual effect of trypsin on channel gating and on the recruitment of near-silent channels was confirmed by experiments using the beta518C mutant ENaC which can be converted to a channel with an open probability of nearly one by exposure to a sulfhydryl reagent. Interestingly, the gammaK181A mutation results in the spontaneous appearance of a 67 kDa fragment of the gamma-subunit in the plasma membrane which can be prevented by a furin inhibitor and also occurs after channel activation by extracellular trypsin. This suggests that the mutation promotes channel cleavage and activation by endogenous proteases. This would lower the pool of near-silent channels and explain the constitutive activation and reduced responsiveness of the mutant channel to extracellular proteases. We conclude that the mutated site (K181A) affects a region in the gamma-subunit of ENaC that is functionally important for the activation of near-silent channels by extracellular proteases.

Protein intake during the period of complementary feeding and early childhood and the association with body mass index and percentage body fat at 7 y of age. - Günther, AL; Buyken, Anette; Kroke, A (Am J Clin Nutr)

Breakfast glycemic index affects subsequent daily energy intake in free-living healthy children. - Buyken, Anette; Trauner, K; Günther, AL; Kroke, A; Remer, T (Am J Clin Nutr)

How early dietary factors modify the effect of rapid weight gain in infancy on subsequent body-composition development in term children whose birth weight was appropriate for gestational age. - Karaolis-Danckert, N; Günther, AL; Kroke, A; Hornberg, C; Buyken, Anette (Am J Clin Nutr)

Early protein intake and later obesity risk: which protein sources at which time points throughout infancy and childhood are important for body mass index and body fat percentage at 7 y of age? - Günther, AL; Remer, T; Kroke, A; Buyken, Anette (Am J Clin Nutr)

Pattern of beverage consumption and long-term association with body-weight status in German adolescents – results from the DONALD study - Libuda, Lars; Alexy, Ute; Sichert-Hellert, Wolfgang; Stehle, Peter; Karaolis-Danckert, Nadina; Buyken, Anette; Kersting, Mathilde (British Journal of Nutrition)
In the present study the relationship between the consumption of different beverage groups and body-weight status in 5 years of study participation in German adolescents was investigated. We used anthropometric and dietary data from 3 d weighed records of 244 subjects between 9 and 18 years of age participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study. Only subjects with at least four out of six possible weighed dietary records were considered. A repeated-measures regression model (PROC MIXED) was used to analyse the effect of beverage consumption on body-weight status. BMI standard deviation scores (BMI-SDS) and body fat percentage (%BF) were chosen as the dependent variables. In boys, energetic beverage consumption was not associated with BMI-SDS or %BF, neither cross-sectionally nor prospectively. In girls, baseline consumption of energetic beverages did not predict baseline BMI-SDS, baseline %BF, or change in either variable over the study period. However, an increase in energetic beverage consumption over the study period was associated with an increase in BMI-SDS (+0.070 SDS/MJ increase in energetic beverage consumption; P = 0·01). Separate consideration of regular soft drinks and fruit juices revealed that, in girls, BMI-SDS increased with increased fruit juice consumption (+0·096 SDS/MJ increase in fruit juice consumption; P = 0·01), and to a lesser extent with regular soft drink consumption (+0·055 SDS/MJ increase in regular soft drink consumption; P = 0·08). In conclusion, these results suggest that an increase in energetic beverage consumption may result in weight gain, at least in adolescent girls.